2022
DOI: 10.1136/bmjgh-2022-010713
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of COVID-19 on child and adolescent mental health: an overview of systematic reviews

Abstract: IntroductionTo control the spread of COVID-19, mitigation strategies have been implemented globally, which may have unintended harmful effects on child and adolescent mental health. This study aims to synthesise the indirect mental health impacts on children and adolescents globally due to COVID-19 mitigation strategies.MethodsWe included relevant reviews from MEDLINE, Embase, PsycINFO, LILACS, CINAHL, The Cochrane Library and Web of Science until January 2022 that examined the impact of COVID-19-related lockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Providing efficient and accessible systemic family therapies is needed, given unmet service needs in child mental health (Merikangas et al, 2011), which have intensified since the start of the COVID‐19 pandemic (Harrison et al, 2022; Madigan et al, 2023). Brief therapies effectively treat a range of disorders from early childhood to late adolescence (Schleider & Weisz, 2017), with evidence that briefer therapies are as effective, or more effective, than lengthier ones (Bakermans‐Kranenburg et al, 2003; Weisz et al, 2017).…”
Section: A Call For Brief Systemic Therapiesmentioning
confidence: 99%
“…Providing efficient and accessible systemic family therapies is needed, given unmet service needs in child mental health (Merikangas et al, 2011), which have intensified since the start of the COVID‐19 pandemic (Harrison et al, 2022; Madigan et al, 2023). Brief therapies effectively treat a range of disorders from early childhood to late adolescence (Schleider & Weisz, 2017), with evidence that briefer therapies are as effective, or more effective, than lengthier ones (Bakermans‐Kranenburg et al, 2003; Weisz et al, 2017).…”
Section: A Call For Brief Systemic Therapiesmentioning
confidence: 99%
“…Because of the pandemic, many populations have experienced important indirect effects, including adverse impacts on health outcomes due to the disruptions in health services and mental health effects arising from physical distancing and school closures, among others. 8 These impacts were particularly experienced by vulnerable populations in low-and middle-income countries (LMICs). The pandemic also laid bare fundamental weaknesses in national, regional, and global provisions for emergency prevention, preparedness, and response.…”
Section: A Changing Landscapementioning
confidence: 99%
“…Many children have experienced heightened mental health problems since the onset of the pandemic (Glynn et al, 2021; Panchal et al, 2021). Across 18 systematic reviews of studies that examined COVID-19-related lockdowns and mitigation measures in relation to child mental health, the global pooled prevalence for each of depression and anxiety was 32%, an increase in comparison to prepandemic estimates (Harrison et al, 2022). Other studies have found an increase in children’s externalizing behaviors (e.g., hyperactivity and conduct problems; Giannotti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%